Improvement science and school leadership: the precarious path to dynamic school improvement - Viano, Samantha; Shahrokhi, Farnoosh; Hunter, Seth B. (Frontiers in Education, 2024)
School systems have increasingly turned to continuous improvement (CI) processes because traditional school improvement plans (SIPs) have resulted in neither reaching set goals nor maintaining performance in challenging times. Improvement science is one way of enacting CI that combines CI with networked improvement to encourage educational equity and build organizational resilience. This study examines the efforts of a school district in the United States to use improvement science to transition their static SIPs to a dynamic process in their underperforming schools. Using a case study design with observations and interviews, we find several sensemaking mechanisms acted as mediators between organizational learning and authentic improvement science implementation. The complexity of improvement science often inhibited sensemaking given time and resource constraints before and during the COVID-19 pandemic, leading to participants often reporting improvement science as too inefficient for their needs. Schools that more successfully integrated improvement science into SIPs saw the value of a systematic approach to SIPs, had interest in distributed leadership, and saw improvement science as advancing equity. This study provides insight into the utility of improvement science as a tool to build organizational resilience as part of school improvement while documenting the many difficulties school improvement teams have in shifting away from static school improvement practices.